2018
DOI: 10.1088/1361-6544/aaba3c
|View full text |Cite
|
Sign up to set email alerts
|

Global Solutions for the zero-energy Novikov–Veselov equation by inverse scattering

Abstract: Using the inverse scattering method, we construct global solutions to the Novikov-Veselov equation for real-valued decaying initial data q 0 with the property that the associated Schrödinger operator −∂ x ∂ x + q 0 is nonnegative. Such initial data are either critical (an arbitrarily small perturbation of the potential makes the operator nonpositive) or subcritical (sufficiently small perturbations of the potential preserve non-negativity of the operator). Previously, Lassas, Mueller, Siltanen and Stahel prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In particular, the solutions Q n,0 do not satisfy the conditions imposed in Music and Perry's [33] work.…”
Section: About the Global Well-posedness Problemmentioning
confidence: 96%
See 1 more Smart Citation
“…In particular, the solutions Q n,0 do not satisfy the conditions imposed in Music and Perry's [33] work.…”
Section: About the Global Well-posedness Problemmentioning
confidence: 96%
“…Those spectral properties are satisfied, in particular, under some small-norm assumptions on initial data. Very recently, Music and Perry [33] showed that in the case of zero energy, if the initial datum v 0 has enough regularity in weighted Sobolev spaces and is such that the associated Schrödinger operator −∆ x,y +v 0 is critical or subcritical (i.e., nonnegative), then N V 0 (E = 0) has a global solution. Schottdorf [39] showed in his Ph.D. thesis that the modified NV equation has small global solutions in L 2 (R 2 ), by making use of suitable Koch-Tataru spaces (see also a previous work of Perry [36]).…”
Section: About the Global Well-posedness Problemmentioning
confidence: 99%
“…The precise meaning of this statement is the subject of a lively discussion, see e.g. [11,12,27,28,30,32]. As for (KdV), smooth and -in case of R 2 being their domain -rapidly decreasing solutions of (NV) satisfy a whole sequence of conservation laws: Integration of the equation over R 2 or T 2 gives that u(x, y, t)dxdy = const.…”
Section: Introductionmentioning
confidence: 99%
“…The first is the inverse scattering method, which has the great advantage of leading to some global existence theorems and to a solution formula. To the best of our knowledge, the most advanced results in this direction are those of Perry [32,Theorem 1.6] and of Music and Perry [30,Theorem 1.2], who built on earlier works [15,29] of Music and of Grinevich and Manakov. The data are assumed to belong to some weighted Sobolev space of fairly high regularity and to lie in the image of the Miura map, or to satisfy a certain (sub-)criticality condition, see Definition 1.1 in [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation